Nonlinear dynamics of (2+1)-dimensional Bogoyavlenskii-Schieff equation arising in plasma physics - Ismael, Hajar F.; Bulut, Hasan (Wiley, 2021)
In this literature, the dynamic characteristics of the Bogoyavlenskii-Schieff equation in (2 + 1)-dimension that arises in plasma physics are studied. Several characteristics of multi-soliton solutions, complex rogue wave, M-lump solutions, fusion solutions, and interaction phenomena between M-lump and soliton solutions also with a fusion solution are discussed. A logarithmic variable transform is used to convert the studied nonlinear equation to a Hirota trilinear form. For all solutions, three-dimensional figures are presented to more understand its dynamic behaviors. All findings are recent, and no experts have reported them.
Keywords: Bogoyavlenskii– Schieff equation; Hirota trilinear form; M? lump solutions; multi? soliton solutions